Meningkatkan Keterampilan Membaca Pemahaman Dengan Metode Cooperative Integrated Reading And Composition (CIRC) Di Sekolah Dasar - Bahri, Syaiful; Muhammad Azlin , Dico (Science and Education Journal (SICEDU), 2024)
This study aims to improve reading comprehension skills in Indonesian language lessons for fourth grade students at State Elementary School 001 salo by using the CIRC method. This type of research is classroom action research with the research subjects of fourth grade students at Elementary UPT SD Negeri 001 Salo, which totaled 19 students. The object of this research is to examine students' reading comprehension skills with the CIRC method. Data collection techniques Data collection techniques were observation, interview, test, and documentation. Data analysis techniques using qualitative and quantitative descriptive analysis. Research results The results showed that the application of the CIRC method can improve skills and The learning process of reading comprehension for fourth grade students at State Elementary School 001 Salo. From the improvement of this action, there was an improvement in the process, which can be seen in the condition of students who are more active in learning activities. The process of improvement can be seen in the condition of students who are more active in learning activities. Process improvement has a positive impact on improving product quality. This is based on the fact that the fact that the reading comprehension test increased, as evidenced by the average student score of 55. Average of 55, with the achievement of classical completeness of 21%, post-action cycle I of 66.31 with the achievement of classical completeness of 42%, post-action cycle 2 of 66.31 with the achievement of classical completeness of 42%, and post-action cycle 2 of 82.1 with classical completeness of 84%.